Science as psychology : sense-making and identity in science practice - Osbeck, Lisa M., 1962- (New York : Cambridge University Press, 2011)
'Science as Psychology reveals the complexity and richness of rationality by demonstrating how social relationships, emotion, culture, and identity are implicated in the problem-solving practices of laboratory scientists. In this study, the authors gather and analyze interview and observational data from innovation-focused laboratories in the engineering sciences to show how the complex practices of laboratory research scientists provide rich psychological insights, and how a better understanding of science practice facilitates understanding of human beings more generally. The study focuses not on dismantling the rational core of scientific practice, but on illustrating how social, personal, and cognitive processes are intricately woven together in scientific thinking. The authors argue that this characterization illustrates a way of addressing the integration problem in science studies - how to characterize the fluid entanglements of cognitive, affective, material, cultural, and other dimensions of discovery and problem solving. Drawing on George Kelly's'person as scientist' metaphor, the authors extend the implications of this analysis to general psychology. The book is thus a contribution to science studies, the psychology of science, and general psychology'--Provided by publisher.
Machine generated contents note: 1. Introduction: science and persons; 2. Methods of study; 3. The problem-solving person; 4. The feeling person; 5. The positioning person; 6. The person negotiating cultural identities; 7. The learning person; 8. Epilogue: science as psychology: a tacit tradition and its implications.
Includes bibliographical references and index.
Keywords: Engineering -- Research; Problem-solving -- Social aspects